2020
DOI: 10.1590/0037-8682-0594-2019
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of interferon-free treatments for patients with early-stage genotype 1 hepatitis C virus in Brazil

Abstract: Introduction: We conducted a cost-utility analysis of available interferon-free treatments for patients with early-stage genotype 1 chronic hepatitis C based on a Brazilian public health system perspective. Methods: A Markov model was derived using a cohort of stage F0-F2 patients treated as recommended by the Brazilian national guidelines. Results: Glecaprevir plus pibrentasvir was superior to all other treatments, followed by sofosbuvir plus velpatasvir. Sofosbuvir plus daclatasvir was identified as the leas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Ferreira et al found that the GLE/PIB regimen is costeffective for treating Brazilian patients with HCV genotype 1 infection in the early fibrosis stages. It is superior to the sofosbuvir + velpatasvir regimen and the sofosbuvir + daclatasvir regimen (11). A Japanese study reached a similar conclusion that the GLE/PIB regimen is the best strategy among the four DAA regimens (7).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Ferreira et al found that the GLE/PIB regimen is costeffective for treating Brazilian patients with HCV genotype 1 infection in the early fibrosis stages. It is superior to the sofosbuvir + velpatasvir regimen and the sofosbuvir + daclatasvir regimen (11). A Japanese study reached a similar conclusion that the GLE/PIB regimen is the best strategy among the four DAA regimens (7).…”
Section: Discussionmentioning
confidence: 89%
“…In comparison, the corresponding SVRs when using the first line agents pegylated IFN (pegIFN) + RBV were 57.88% and 81.32% respectively. Studies in Japan and Brazil have indicated that GLE/PIB could be an economical option for HCV treatment given its excellent clinical efficacy (7,11).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the QALYs and costs of the DCV/SOF regimen were more than those of LDV/SOF; however, by comparing the ICER obtained with the threshold, DCV/SOF was more cost-effective than LDV/SOF. Confirming these results, Ruggeri et al ( 2019) conducted a study to assess the cost-effectiveness of two regimens DCV/SOF and LDV/SOF, (51). Moreover, the results of the oneway sensitivity analysis showed that the VEL/SOF regimen was more cost-effective than the two other medical strategies, which were placed in the acceptable range below the threshold and obtained the best results considering the costs.…”
Section: Discussionmentioning
confidence: 94%